The Philippines travel guide - Hicks, Nigel (London New Holland, 2000)
It provides factual information on the different parts of the Philippine archipelago, and as a whole. It features travel tips for potential visitors.
Keywords: Philippines -- Description and travel -- Guidebooks; Philippines -- Maps